Tri Hita Karana as a Basis for Rural Cultural Tourism Marketing Strategy - A.A Made Indra Wijaya Kusuma; Putu Ayu Sita Laksmi; Ketut Winda Pratiwi; I Ketut Johny Pramanda Putra; Pande Gde Bagus Naya Primananda (Information Technology and Science (ITScience), 2026)
Culture-oriented tourism plays a vital role in empowering rural economies and safeguarding local wisdom. However, marketing practices in this sector frequently prioritize commercial appeal rather than embodying indigenous cultural values. This study investigates the influence of cultural tourism marketing strategies on rural destination branding, with the Tri Hita Karana (THK) philosophy serving as a mediating variable. Grounded in value-based marketing and cultural sustainability perspectives, this research emphasizes the integration of local wisdom into destination branding as a strategic intangible asset. Data were collected through a structured Likert-scale survey involving 121 tourism stakeholders and community members in Jatiluwih Tourism Village, a UNESCO World Heritage Site in Bali, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that cultural tourism marketing strategies have a significant positive effect on destination branding. Moreover, Tri Hita Karana values significantly mediate this relationship, indicating that marketing strategies aligned with spiritual harmony (Parhyangan), social cohesion (Pawongan), and environmental balance (Palemahan) strengthen destination brand authenticity and credibility. The results contribute theoretically by extending destination marketing and branding literature through the empirical integration of an indigenous philosophical framework into a structural model. Practically, the findings suggest that rural tourism managers and policymakers should embed cultural and spiritual values into marketing communications to enhance sustainable brand identity, visitor trust, and long-term destination resilience. Overall, this study highlights that culturally grounded marketing strategies are essential for developing authentic and sustainable rural tourism destinations in culturally rich regions.